0702 Phrenic Nerve Stimulation Improves Oxygenation And Quality Of Life In Patients With Central Sleep Apnea And History Of Cerebrovascular Accidents. (27th May 2020) - Schwartz, A R; Khayat, R; Sundar, K M; Germany, R; McKane, S; Costanzo, M
Abstract: Introduction: Central sleep apnea (CSA) is a recognized complication of cerebrovascular accidents (CVA), although CSA treatment in this setting is of uncertain benefit. A recent randomized clinical trial showed that transvenous phrenic nerve stimulation (TPNS, rem edē system, Respicardia Inc.) treats CSA. The clinical impact of TPNS on CSA outcomes in the subgroup of patients with prior CVA was studied. Methods: Six subjects with predominantly CSA and history of CVA >6 months prior to enrollment in the rem edē System Pivotal Trial were analyzed. Patients underwent attended full-night polysomnography prior to TPNS implantation and 6, 12 and 18 months on TPNS therapy. Apnea-hypopnea index (AHI) and sleep metrics were evaluated. The Epworth Sleepiness Scale (ESS) and Patient Global Assessment (PGA) questionnaire were completed at 12 months. Treated patients and former controls (therapy was turned on after 6 months) with 18 months of TPNS therapy were pooled for analysis based on months of therapy. Results: Apnea-hypopnea index decreased from a median of 47 events/hour [interquartile range: 23, 71] at baseline to 15 [4, 24], 17 [6, 48], and 12 [8, 27] at 6, 12, and 18 months. Comparable improvements were also seen in oxygen desaturation index (4%) and arousal index. Central apnea index decreased from 30 [21, 61] to ≤3/hour at each follow up. Compared to baseline, ESS decreased by 5 [-10, -3] and 4 [-8, -4] points at 6 and 12 months, while moderate or markedly improved overall health per the PGA was reported by 4/6 and 3/6 patients, respectively. No patient reported recurrent CVA or transient ischemic attack. Conclusion: Transvenous phrenic nerve stimulation improved sleep, daytime somnolence and quality of life in patients with CSA and prior CVA. Transvenous phrenic nerve stimulation is a novel therapy that may be an option for treating patients with CSA and prior CVA. Support: Respicardia and NIH R01 HL 144859